1971
DOI: 10.1346/ccmn.1971.0190308
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exchangeable Cations on the Sorption of Chlorophyllin By Montmorillonite

Abstract: Abstract--The sorption of commercial K-Cu chlorophyllin by a sample of montmorillonite saturated with different exchange ions was studied. The organic anions are sorbed on external surfaces while K displaces most of the exchangeable cations. The samples sorb the constituents of chlorophyllin selectively and in different amounts, depending on the exchangeable cations of the clay. These also affect the amount of material peptized and the relative orientation and aggregation of the particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Several earlier reports have indicated that porphyrins bind strongly to layered silicate surfaces. Model studies of the role of porphyrins in petroleum diagenesis have shown that various types of free base porphyrins can bind and undergo transalkylation reactions on montmorillonite under simulated geological conditions.3 Also, chlorophyllin has been found to bind to layered silicates, 4 and hemin has been intercalated as the hemin cation in montmorillonite. 5 The intercalation of metalloporphyrins in layered silicate structures could be of some interest for solid-state dioxygen binding and catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier reports have indicated that porphyrins bind strongly to layered silicate surfaces. Model studies of the role of porphyrins in petroleum diagenesis have shown that various types of free base porphyrins can bind and undergo transalkylation reactions on montmorillonite under simulated geological conditions.3 Also, chlorophyllin has been found to bind to layered silicates, 4 and hemin has been intercalated as the hemin cation in montmorillonite. 5 The intercalation of metalloporphyrins in layered silicate structures could be of some interest for solid-state dioxygen binding and catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…As porfirinas são bem conhecidas por suas aplicações biológicas e catalíticas [25], e é de interesse a absorção e intercalação das porfirinas em lamelas [17]. Estudos da interação de lamelas com porfirinas foram motivados pela ocorrências de porfirinas em sedimentos e depósitos de petróleo [26,27].…”
Section: Porfirinasunclassified